2002
DOI: 10.1074/jbc.m206917200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipoprotein Lipase by Protein Kinase Cα in 3T3-F442A Adipocytes

Abstract: Lipoprotein lipase (LPL) is an important enzyme in adipocyte and lipid metabolism with complex cellular regulation. Previous studies demonstrated an inhibition of LPL activity and synthesis following depletion of protein kinase C (PKC) isoforms with long term treatment of 3T3-F442A adipocytes with 12-O-tetradecanoylphorbol-13-acetate. To identify the specific PKC isoforms involved, we treated cells with antisense oligonucleotides that block expression of specific PKC isoforms. An antisense oligonucleotide to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The change in PKC α mRNA was accompanied by a 50 ± 10% decrease in PKC α protein as measured by Western blot analysis of cell lysates. Although there was no decrease in LPL mRNA expression in PKC α antisense-treated cells, LPL synthesis and protein expression were inhibited as demonstrated previously [11], and LPL activity was inhibited by 52 ± 12% (Figure 1). …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The change in PKC α mRNA was accompanied by a 50 ± 10% decrease in PKC α protein as measured by Western blot analysis of cell lysates. Although there was no decrease in LPL mRNA expression in PKC α antisense-treated cells, LPL synthesis and protein expression were inhibited as demonstrated previously [11], and LPL activity was inhibited by 52 ± 12% (Figure 1). …”
Section: Resultssupporting
confidence: 83%
“…LPL is also translationally repressed following depletion of cellular PKC (protein kinase C), either through prolonged treatment with phorbol esters or through the use of antisense oligonucleotides to PKC α [11]. This PKC α -mediated inhibition of LPL translation also involved the 3′UTR of the LPL mRNA, although the precise nature of the RNA-binding protein is not known.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that other studies have also reported an important contribution of PKCs toward LPL secretion in macrophages and adipocytes. [37][38][39] Diabetes is known to activate a number of PKC isoforms. 40,41 We attempted to activate PKC by duplicating the plasma concentrations of glucose and FA observed after DZ, and study its influence on cardiac LPL.…”
Section: Kim Et Al Control Of Cardiac Lpl Secretion During Diabetes 257mentioning
confidence: 99%
“…A recent report suggested that LPC contributes to the activation of a pro-inflammatory endothelial phenotype, an effect requiring inputs from protein kinase C (PKC) [94]. Interestingly, PKC has been implicated in the regulation of LPL in adipocytes [95] and macrophages [96]. Furthermore, in macrophages, leptin induced augmentation of LPL gene expression involved PKC activation [97].…”
Section: Lysophospholipidsmentioning
confidence: 96%